Policies to Improve Substance Use Disorder Treatment with Telehealth During the COVID-19 Pandemic and Beyond - Drake, Coleman (J Addict Med, 2020)
The COVID-19 pandemic has created an urgent need to expand access to substance use disorder (SUD) treatment through telehealth. A more permanent adoption of tele-SUD treatment options could positively alter the future of SUD treatment. We identify four steps that will help to ensure a broader transition to telehealth will be successful in improving the health outcomes of patients with SUDs. These steps are: (1) investing in telehealth infrastructure to enable health care providers and patients to use telehealth; (2) training and equipping providers to provide SUD treatment through telehealth; (3) providing patients with the financial and social support, hardware, and training necessary to use telehealth; (4) making temporary changes to telehealth law and regulation permanent. We believe these four steps will be critical to initiating SUD treatment for many persons that have yet to receive it, and for preserving SUD treatment continuity for millions of other patients both during and after the pandemic.